Bibliometric Analysis of Procrastination Among Gen Z in the Workplace - Wibowo, Ghita Devina (Westscience Press, 2025)
Examining procrastination in the workplace, particularly concerning Generation Z, has attracted considerable attention. This paper aims to perform a bibliometric review of publications related to workplace procrastination, identify thematic patterns, and explore the influence of psychological factors on procrastination behaviors, especially within the Generation Z group. One hundred seven studies published between 1992 and 2025 were analyzed using tools like VOSviewer and Mendeley. The findings categorize the research into three primary clusters: Procrastination related to the workplace, psychological elements such as stress and self-control, and decisional procrastination. This paper also addresses gaps within the existing body of literature. It proposes potential areas for future research on the impact of workplace culture, leadership styles, and other organizational factors on procrastination, particularly among Generation Z workers.